PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA MELALUI KINERJA GURU PADA SDN 005 PENAJAM - jurnalmap map; Uulindayah ÔÇì; Indra Prasetyo; Chamariyah ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
ABSTRACT This study aims to describe the work environment, motivation, work, and job satisfaction of teachers and employees at SDN 005 Penajam and to find out the contents of work for teacher job satisfaction, the influence of the work environment on teacher satisfaction, and the effect of work on teacher performance. teacher work environment. This study uses a quantitative approach and type of explanatory research. The population in this study were all teachers of SDN 005 Penajam. The research sample was played by 30 teachers. The results of this study indicate that work and work environment are significant towards teacher job satisfaction at SDN 005 Penajam. Work motivation and work environment are significant towards teacher performance at SDN 005 Penajam. Performance has a significant effect on teacher job satisfaction at SDN 005 Penajam. Work motivation and work environment have a positive effect on job satisfaction through teachers at SDN 005 Penajam. Keywords: work, work environment, performance, job satisfaction